Perfil anticonvulsivante de produtos naturais oriundos de plantas e avaliação do efeito farmacológico de γ-TERPINENO em modelos animais de convulsão - Pina, Lícia Tairiny Santos (2022)
Epilepsy is a neurological disease responsible for cognitive, psychological and social problems. Medical therapy is limited due to the high rate of drug resistance (more than 30% of patients with epilepsy) and adverse effects generated, requiring the search for new therapeutic options. In this context, the plant-based natural products constitute a strategy for the treatment of various pathological conditions, including seizures. Therefore, the aim of this study was to compile scientific and technological evidence of the anticonvulsant activity of plant-based natural products through a systematic and a patent review, and to evaluate the anticonvulsant effect of γ-terpinene (γ-TPN) in an animal model of seizure. The systematic literature search was performed in the PubMed, Web of Science and Scopus databases and gathered the findings published on 51 papers on the anticonvulsant activity of 35 monoterpenes, as well as their action on GABAa receptors, cationic channels and neuronal damage reduction. The search for patents was carried out in one of the largest patent databases (ESPACENET) and covered publications patented between 2015 and 2020 involving the use of plant products (extracts, essential oils and isolated compounds) with proven activity in epilepsy/seizure models. Sixteen selected patents reported the use of 10 extracts, 1 essential oil and 8 compounds isolated from plants as future therapeutic strategies for seizures. The anticonvulsant effect of γ-TPN was evaluated in a model induced by pentylenetetrazol (PTZ, 80 mg/kg, i.p.) and pilocarpine (380 mg/kg, i.p.) in male Swiss mice (CEPA: 25/2018). For this, the treatments (10, 50 and 100 mg/kg, p.o.) were carried out 60 minutes before the administration of the convulsant agent. However, the γ-TPN, in the administration route used and tested doses, was not able to reduce the latency time for seizure onset after administration of PTZ and pilocarpine due to their low solubility and pharmacokinetic properties. From the foregoing, it is possible to conclude that plant-derived products are promising strategies in the control and treatment of seizures and that further studies evaluating the neurological potential of γ-TPN need to be carried out.